Mapping for indoor walking path using mobile laser scanning / Nurfadhilah Ruslan … [et al.] - Ruslan, Nurfadhilah; Rosadlan, Nur Syazwani; Naharudin, Nabilah; Abd Latif, Zulkiflee (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Walkability is one of the keys in developing a sustainable city. These days, many cities have considered enhancing walkability for pedestrian paths to ensure the seamless walking experience for people to reach their destination. Therefore, it is very important to have a good walking environment so people will find walking pleasant. However, there was a lack of studies attempting to include indoor walking environments in their walkability analysis. Most of them only consider outdoor walking paths. This might be due to the difficulties in modelling the indoor walking environment. With the advance technology of laser scanning, it might be possible to develop an indoor walking path by using point clouds collected for a building. The usage of point clouds could make it easier to segment the building elements and obstacles in an indoor environment. In order to produce an indoor map, it is important to reconstruct the building elements such as wall, ceiling, window and door. Therefore, this paper aims to generate the indoor walking path using laser scanning point clouds showing all the options to the pedestrians.